DAMPAK PENERAPAN KONSERVASI LAHAN TERHADAP RAGAM TANAMAN DAN PENDAPATAN USAHATANI HUTAN RAKYAT DI WILAYAH PERBUKITAN KABUPATEN BANTUL - Sutrisno Sutrisno; Sri Widodo; Slamet Hartono (Agro Ekonomi, 2006)
This research aims at identifity the implementation level of land conservation by community forestry farmers, it also aims at identifying the factors that affect the implementation level of land conservation and finding out the influences of land conservation implementation towards variety of plants and farming income of community forestry. This research takes place in Dlingo subdistrict is conducted using descriptive method, with the sample of 60 farmers chosen using stratified ransom sampling. Used is primary data that is analyzed in tabulation and linear regression. The implementation of land conservation conducted by community forestry farmers can be categorized into vegetative and mechanic techniques. The level of land conservation implementation in general is categorized as high. However, two are low i.e, burying the plant waste into the ground and growing predator plants. There is one categorized as medium level is cutting wood rotationally. Linear regression analysis  shows that the real factors affecting the implementation level of land conservation by community forestry farmers are perception, attitude, geographical location, and the intensity of extension education. The land conservation implementation by farmers has positive and real effects towards the variety of plants but does not have real effects towards the farming income. The analysis shows that variety of plant has positive and real effects towards the farming income of community forestry.